The Bloomsbury Companion to metaphysics - Manson, Neil A.; Barnard, Robert W. (Bloomsbury Companions, 2015)
Bridging the gap between the familiar figures of the history of philosophy and the technical approaches favoured by contemporary philosophers, The Bloomsbury Companion to Metaphysics introduces the key ideas and debates needed to understand analytic metaphysics. Presenting an effective syllabus for an introductory course in contemporary metaphysics, this companion brings together a team of leading metaphysicians. It begins with a comprehensive introduction to methodological problems and methods, before tackling the perennial metaphysical questions surrounding core topics such as: • Modali